TATA KELOLA KEUANGAN RUMAH TANGGA SEJAHTERA DAN MANDIRI DI DESA WOKAM - Piter Arson Welay; Selva Temalagi (Jurnal Padamu Negeri, 2025)
This Community Service (PkM) program aims to enhance the understanding of Wokam Village residents regarding the management of prosperous and independent household finances. The main problems faced by the community include the imbalance between income and expenses, low saving awareness, and weak family financial planning. The implementation methods consisted of field observation, problem identification, education, and interactive discussions. The activity was carried out on December 19, 2024, in Wokam Village, attended by 30 participants, mostly housewives. The results showed an improvement in participants’ knowledge and awareness of effective household financial management through budgeting, spending control, and saving plans. This program is expected to serve as an initial step toward building financially independent families and improving community welfare in the island region.